2021
DOI: 10.1111/acem.14357
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a care transitions intervention for older adults discharged home from the emergency department: A randomized controlled trial

Abstract: Background Improving care transitions following emergency department (ED) visits may reduce post‐ED adverse events among older adults (e.g., ED revisits, decreased function). The Care Transitions Intervention (CTI) improves hospital‐to‐home transitions; however, its effectiveness at improving post‐ED outcomes is unknown. We tested the effectiveness of the CTI with community‐dwelling older adult ED patients, hypothesizing that it would reduce revisits and increase performance of self‐management behaviors during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
1
19
1
Order By: Relevance
“…Recent work has highlighted an overall lack of high-quality data to guide recommendations about optimal ED-to-community care transition strategies for older adults. [14][15][16][17][18] With the extant literature demonstrating limited relevant qualitative data, 19,20 hypothesis-generating qualitative research may identify potential opportunities to improve care transitions, which could help generate novel ED-to-community care transition interventions to be tested and implemented among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has highlighted an overall lack of high-quality data to guide recommendations about optimal ED-to-community care transition strategies for older adults. [14][15][16][17][18] With the extant literature demonstrating limited relevant qualitative data, 19,20 hypothesis-generating qualitative research may identify potential opportunities to improve care transitions, which could help generate novel ED-to-community care transition interventions to be tested and implemented among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to transition interventions at Brigham Health and Harborview Medical Center, we found that early follow‐up combined with intensive social resource assistance significantly reduced subsequent ED visits versus a comparator group 15,16 . Other similar care transition interventions found no difference in the 30‐day ED revisits, but primary care engagement was improved 3,17 . Regarding subsequent hospitalization, we found that CTC participants were slightly more likely to be hospitalized within 30 days, though the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 49%
“…This in‐person care and hand‐off to primary care clinicians may help stabilize patients' medical conditions and reduce disease exacerbations resulting in ED revisit. This concept is supported by studies that found interventions involving patient education but not on‐site medical treatment improved follow‐up behavior (outpatient follow‐up, red flag knowledge) but had no effect on subsequent ED utilization 3,19 . Second, CTC appointments are scheduled prior to ED discharge.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations